2021
DOI: 10.1038/s41598-021-95140-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high rosuvastatin doses on hepatocyte mitochondria of hypercholesterolemic mice

Abstract: Statins are the cornerstone of therapy for individuals with hyperlipidemia. The aim of this study was to analyze the undesirable effects of mild, moderate and high doses of rosuvastatin in CD-1 male mice who received a cholesterol-rich diet, focusing on the morphological and functional changes on hepatocyte mitochondria. In a mouse model we studied the combined administration of a cholesterol-rich diet along with mild and moderate doses of rosuvastatin (1, 2.5 or 5 mg/kg/day) during several days. After the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Interestingly, in contrast to the control group, the fluvastatintreated flies showed significantly larger mitochondria sizes (Figure 3E) and the number of round-like shaped mitochondria was remarkably higher (Figure 3F). In line with these results, several publications have pointed out that statins cause enlarged and round-like shaped mitochondria [89][90][91][92][93].…”
Section: Chronic Fluvastatin Treatment Induces Phenotypic Changes In ...supporting
confidence: 70%
“…Interestingly, in contrast to the control group, the fluvastatintreated flies showed significantly larger mitochondria sizes (Figure 3E) and the number of round-like shaped mitochondria was remarkably higher (Figure 3F). In line with these results, several publications have pointed out that statins cause enlarged and round-like shaped mitochondria [89][90][91][92][93].…”
Section: Chronic Fluvastatin Treatment Induces Phenotypic Changes In ...supporting
confidence: 70%
“…Previous studies have suggested a link between rosuvastatin treatment and the development of new-onset diabetes (Ostrowska et al, 2015;Salunkhe et al, 2016;Yoon & Lee, 2013); however, the exact processes underlying this adverse effect of rosuvastatin remain unclear. We conducted detailed in vivo and in vitro investigations It should be noted that the doses of rosuvastatin used in the present studies (10 mg/kg in vivo and 25 μM in vitro), chosen based on the literature (Desjardins et al, 2008;Diaz-Zagoya et al, 2021;Mayanagi et al, 2008;Tijeras-Raballand et al, 2010;Zeybek et al, 2011), are much higher than those used in humans (0.1-1 mg/kg, Bjorkhem-Bergman et al, 2011), and that the in vitro concentrations are several orders of magnitude greater than the concentrations of the drug reported in human plasma (1-15 nM, Bjorkhem-Bergman et al, 2011). In this regard, the dose-response experiments showed that the lowest effective concentration of rosuvastatin in inhibiting Akt and GSK3β signaling in the mouse cell line C2C12 was 10 μM, which was ∼100-fold higher than the expected levels in plasma of patients on statins.…”
Section: Discussionmentioning
confidence: 99%
“…The next step was the preparation of liver homogenate by using a homogenizer. After the preparation of homogenate, the assay of HMG-CoA was carried out ( Rao and Ramakrishnan, 1975 , Díaz-Zagoya et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%